PRAKTIK BAHASA INGGRIS DALAM PEMASARAN PRODUK UKM DI DESA LUMBAN PEA TIMUR, KECAMATAN BALIGE KABUPATEN TOBA - Vivi Novalia Sitinjak; Pahotan Sinaga; Milisi Sembiring; Esron Ambarita; Nurlaidy Joice Simamora; Harkiman Racheman; Karana Jaya Tarigan; Bernat Sitorus; Chichi Josephine F. Manalu (Universitas Methodist Indonesia, 2022)
Community service (Pengabdian kepada Masyarakat) is training and educating the public to improve the quality of people. Community service is a training process to give information, training and mentoring. This paper entitled “Praktik Bahasa Inggris dalam Pemasaran Produk UMKM di Desa Lumban Pea Timur, Kecamatan Balige Kabupaten Toba.” Conducted on 8-11 June 2022. This objective of community service is to exercise the society in speaking English, to increase their economy. This community service using discussion, sharing ideas and practice.